Benefit Incidence Analysis on Bidikmisi Program - Innayah, Nur; Arianti, Fitrie (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
One of the ways to improve the quality of human resources is by providing educational assistance programs for students who wish to continue their education to higher education. Bidikmisi is one of the scholarship programs provided by the government in helping prospective students, especially those who are less fortunate, to pursue higher education.This study focuses on analyzing the impact of the application of the Bidikmisi scholarship using the Benefit Incidence Analysis (BIA) method. The data used in this study are primary data. Data was collected using a survey method through questionnaires distributed to Bidikmisi students who were the sample. The sample used is Bidikmisi students with active status at Diponegoro University from class 2017, 2018 and 2019. The results of this study indicate that the Bidikmisi program at Diponegoro University is a progressive policy. The university as the organizer of the bidikmisi program is considered appropriate in providing the obligations of bidikmisi recipients to bidikmisi students at Diponegoro University. The group of students with the lowest level of parental income gets a 33 percent distribution of benefits from the Bidikmisi program funds. The concentration curve lies above the 45 degree diagonal line, so the 10 percent of students with the lowest income level (first quintile) in the population receive more than 10 percent of the benefits of the subsidy so that the distribution of benefits can be said to be progressive in absolute terms